2002
DOI: 10.1002/jcb.10267
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cultured progenitor cells from human marrow stroma

Abstract: The marrow stromal cells (MSC) are essential for regulation of bone remodeling and hematopoiesis. It is of prime importance to isolate MSC and to expand the proliferating cells ex vivo. In this study, we analyzed cultured MSC for various cellular parameters, including cell morphology, cell cycle, and expression of cell surface antigens by flow cytometry. MSC were divided based on cell size to small (S-cells) and large (L-cells) and were visualized by light and electron microscope. The S-cells were proliferatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 30 publications
1
47
0
Order By: Relevance
“…Recently, it has been shown that articular cartilage in rabbits grows appositionally until puberty implying a progenitor cell population located at the cartilage surface in young animals [Hunziker et al, 2007]. This zone consists of small cells and it has been demonstrated in other tissues that small cells express known markers for progenitor cells [Shur et al, 2002]. Additionally, surface cells are characterized by their Notch1 expression [Dowthwaite et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that articular cartilage in rabbits grows appositionally until puberty implying a progenitor cell population located at the cartilage surface in young animals [Hunziker et al, 2007]. This zone consists of small cells and it has been demonstrated in other tissues that small cells express known markers for progenitor cells [Shur et al, 2002]. Additionally, surface cells are characterized by their Notch1 expression [Dowthwaite et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…One characteristic of the cells in this zone is their small size compared to cells found in deeper layers of articular cartilage [Hidaka et al, 2006]. Small cellular size is characteristic for mesenchymal progenitor cells, while larger cells represent a more differentiated state [Shur et al, 2002]. The small cells located in the surface zone of articular cartilage might thus have progenitor cell characteristics with improved capacity to produce hyaline cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…by guest www.bloodjournal.org From Because marrow stromal cells are a heterogenous cell population and comprise fibroblast-like cells, macrophages, and endothelial cells, we next determined if the differences between MM patient-derived and normal stromal cells were due to a change in the distribution of cell types present in the stromal cell preparations, such as enrichment or loss of a particular cell type that affected the capacity of the stromal cell preparations to stimulate the growth of MM cells. Both MM and normal stromal cells contained similar percentages of cells that expressed CD63 (88.5 Ϯ 1.4 vs 88.4 Ϯ 1.8, mean Ϯ standard deviation [SD] for healthy vs MM patients, n ϭ 5) and CD51 (86 Ϯ 0.5 vs 90 Ϯ 3, mean Ϯ SD for healthy vs MM patients, n ϭ 5) 23,24 and that had low expression of CD14 (11 Ϯ 1 vs 12 Ϯ 0.3, mean Ϯ SD for healthy vs MM patients, n ϭ 5; Figure 1D). The hematopoietic cell marker for the monocyte lineage (CD11b) was not detected in either stromal cell preparation (data not shown).…”
Section: Characterization Of Marrow Stromal Cells From Healthy Patienmentioning
confidence: 99%
“…Ex vivo primary cultured human mesenchymal marrow cells (MSC) [Shur et al, 2002] and MBA-15, a mouse marrow stromal derived cell line [Benayahu et al, 1989] were cultured in growth medium containing Dulbecco's modified essential medium (DMEM) (Gibco) with the addition of 10% heat-inactivated fetal calf serum (FCS, Biological Industries, Bet-Haemek, Israel). COS-7 cells were grown in DMEM medium supplemented with 5% FCS.…”
Section: In Vitro Culturementioning
confidence: 99%